2018
DOI: 10.1155/2018/2518676
|View full text |Cite
|
Sign up to set email alerts
|

C60 Fullerene Prevents Restraint Stress‐Induced Oxidative Disorders in Rat Tissues: Possible Involvement of the Nrf2/ARE‐Antioxidant Pathway

Abstract: The effects of C60FAS (50 and 500 μg/kg) supplementation, in a normal physiological state and after restraint stress exposure, on prooxidant/antioxidant balance in rat tissues were explored and compared with the effects of the known exogenous antioxidant N-acetylcysteine. Oxidative stress biomarkers (ROS, O2·−, H2O2, and lipid peroxidation) and indices of antioxidant status (MnSOD, catalase, GPx, GST, γ-GCL, GR activities, and GSH level) were measured in the brain and the heart. In addition, protein expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 68 publications
4
33
0
8
Order By: Relevance
“…Since water-soluble nanoscale pristine C 60 fullerenes are powerful antioxidants [56,57], presumably, their ability to scavenge free radicals is one of the main mechanisms for 9 Oxidative Medicine and Cellular Longevity providing antifibrotic activity. Indeed, the main three pathways responsible for liver fibrogenesis are growth arrestspecific gene 6 serum protein (Gas6)/Axl, transforming growth factor β (TGF-β)/Smad, and Wnt signaling [4], and all of them have been shown to be upregulated by ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Since water-soluble nanoscale pristine C 60 fullerenes are powerful antioxidants [56,57], presumably, their ability to scavenge free radicals is one of the main mechanisms for 9 Oxidative Medicine and Cellular Longevity providing antifibrotic activity. Indeed, the main three pathways responsible for liver fibrogenesis are growth arrestspecific gene 6 serum protein (Gas6)/Axl, transforming growth factor β (TGF-β)/Smad, and Wnt signaling [4], and all of them have been shown to be upregulated by ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their hydrophilic properties and the ability to scavenge free radicals, fullerenols may, in the future, provide a serious alternative to the currently used pharmacological agents in chemotherapy, treatment of neurodegenerative diseases, and radiobiology. Water-soluble derivatives of fullerenes (fullerenols and malonic acid derivatives) scavenge ROS more efficiently than conventional antioxidants [101][102][103][104][105][106]. Therefore, hydrophilic fullerene derivatives are promising candidates for the use as neuroprotective and antioxidant agents, as confirmed in electrophysiological studies indicating that two fullerene derivatives (C60(OH)12 and C60 (OH)18-20O3-7) showed excellent antioxidant properties (confirmed by electron paramagnetic resonance).…”
Section: Technologies For Screening Bioactive Molecules To Target Mitmentioning
confidence: 92%
“…Ãлавную роль в инициации воспалительных реакций играет каскадное, прогрессирующее увеличение свободнорадикальных компонентов. Способность С 60 -фуллерена эффективно нейтрализовать свободные радикалы [1][2][3][22][23][24], по нашему мнению, является основной причиной полученных позитивных результатов применённой терапии.…”
Section: результаты и обсуждениеunclassified